Studi Literatur: Strategi Pengamanan Siber dalam Menghadapi Cyber Crime - Wahyuni Susilowati; Agussalim Agussalim (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
In the current digital era, cybersecurity of data and information systems. The threat of attacks, or , is a form of threat that continues to grow along with advances in technology. This research aims to learn about cybersecurity strategies in dealing with . The method used in this research is a literature review. This journal was prepared based on an analysis of research results from various journals accessed through secondary data sources, namely the Google Scholar database, and e-resources from Springer, Cambridge, and Taylor and Francis. The research results show that implementing technology such as encryption, multifactor authentication, and user training, are some of the effective steps that have been proven to reduce risk. However, challenges in implementing this strategy remain, both from a technical and non-technical perspective, which require special attention from researchers and practitioners in the field of cyber security.